Debt determinants of shariah approved firms: Empirical evidence from Malaysia - Ramli, Nurshamimitul Ezza; Haron, Razali (2016)
The issue of high reliance on debt has raised major concern since the impact of debt has created several downfalls of US’s big corporation such as Enron and Lehman Brothers. At wider scope, the impact of debt may also be evidenced by the Greek Depression in the year 2009. Various studies have been conducted to explain which factors that determine debt of the firms, given different setting of periods, countries and methodologies. Uniquely, this study focuses on the Shariah approved firms, firms which stocks are Shariah approved accordance to the Malaysia’s Securities Commission. This study covers a balanced panel of 239 Shariah approved firms listed on the Bursa Malaysia for the period of analysis from 2000 to 2014. To meet its objective, this study employs a static panel regression model which includes the pooled OLS, random effect model (REM) and fixed effect model (FEM). The study also conducts a robustness test to the empirical model. Several factors have been examined and the result shows that certain firm-specific variables like growth opportunity, size, bankruptcy risk, non-debt tax shield (NDTS) and Herfindahl-Hirschman Index, while the macro variables that include inflation, GDP and economic crisis are the robust evidence in determining the debt level of Shariah approved firms in Malaysia. In contrast with the prior studies that focuses on the non-Shariah approved firms, the output from this study provides new insight and understanding on the debt determinants of Shariah approved firms. This study also largely contributes in terms of the sampling selection in which a firm must be consistently being Shariah approved during the period of analysis.